Antiplasmodial Assessment of Artemether- Lumefantrine/Ivermectin on Mice Infected with Plasmodium berghei - Georgewill, Udeme Owunari; Liverpool, Ebiladei; Adikwu, Elias (Asian Journal of Biological and Life Sciences, 2020)
Substantial progress made in the fight against malaria has been undermined by challenges including drug resistance instigating the search for new antimalarial drugs or the repurposing of already approved drugs. This study evaluated the antiplasmodial activity of ivermectin (IM) in combination with artemether/lumefantrine (A/L) in a mice model infected with Plasmodium berghei. Parasitized (Plasmodium berghei) adult mice weighing 23-28g were used. The mice were grouped and treated orally with 1M (0.17 mg/kg), A/L (2.3/13.7mg/kg) and A/L/IM daily in curative, suppressive and prophylactic tests. The negative control (NC) was treated orally with normal saline (0.2ml) whereas the positive control was treated orally with chloroquine (CQ) (10mg/kg). After drug treatment, blood samples were collected and evaluated for percentage parasitemia levels, percentage parasitemia inhibition, lipid and hematologic parameters. Mean survival time was also evaluated. The 4-day curative, suppressive and prophylactic test showed significant decreases in percentage parasitemia levels at IM (0.17 mg/kg) (p<0.01), A/L (2.3/13.7 mg/kg) (p<0.001) and A/L/IM (p<0.0001) when compared to negative control. IM (0.69 mg/kg), A/L (2.3/13.7mg/kg) and A/L/IM increased mean survival time significantly at p<0.05, p<0.01 and p<0.001 respectively when compared to negative control. Red blood cells, packed cell volume, hemoglobin, high density lipoprotein cholesterol levels were increased significantly whereas total cholesterol, white blood cell, low density lipoprotein cholesterol and triglyceride levels were decreased significantly at IM (0.17 mg/kg) (p<0.05), A/L (2.3/13.7mg/kg) (p<0.01) and A/L/IM (p<0.001) when compared to negative control. This study suggests the use of A/L/IM as a viable malaria treatment.
Keywords: Artemether/lumefantrine; Ivermectin; Antimalaria; Mice; Repurposing